Curcuma longa as a Natural Immunomodulator for Preventing infection from COVID 19 With an In Silico Approach - Lely Mauliana; Ahmad Shobrun Jamil; Siti Rofida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
SARS-CoV-2 is a Coronaviridae virus with a single-stranded RNA genome. This virus is highly contagious and spreads rapidly, with mutations occurring at a rapid pace. Various preventive actions have been implemented to prevent the spread of Covid-19 instances. The World Health Organization recommended that everyone clean their hands, masks, and other items in their environment on a frequent basis. As a result of these measures, the virus's transmission will be slowed. Furthermore, keeping one's immune system is critical for limiting the spread of Covid-19. As a result of a weakening immune system, our body's defenses will deteriorate, making us more susceptible to sickness and unable to fight diseases caused by viruses or bacteria. If the immune system is strong, it will recognize and kill viral and bacterial compounds when they are exposed. Immunomodulators, such as natural vitamins and herbs, can help maintain and boost immunity. Indonesia is primarily a farming country. In Indonesia, many different varieties of plants can be grown. Turmeric is an Indonesian medicinal plant that may be found all across the country. Turmeric's ability to act as an immunomodulator has also been proven. As a result, the goal of this study is to determine the usefulness of the active chemicals found in the Curcuma longa plant as a natural immunomodulator in order to avoid mutations of the COVID 19 variation by looking at the background of the current situation. The approach employed in this study is an in silico Molecular Docking test, with the goal of determining the active side of the drug and the value of Binding Affinity from the Docking data. Tissue Pharmacology is used to depict the protein network found in turmeric plants, as well as the substances and diseases that are linked to these proteins. According to the findings, the compound quercetin acts as a ligand for the PIK3CG protein and has a high binding affinity of -7.4. As a result, it can be identified as a substance that acts as a natural immunomodulator in turmeric plants.